Hubungan Tingkat Pengetahuan Dan Sikap Terhadap Tindakan Pencegahan Penyakit Menular Seksual Di Wilayah Kerja Puskesmas Puuwatu - Akifah (STIKES Columbia Asia Medan, 2025)
Sexually transmitted diseases remain a problem at the Puuwatu Community Health Center, where five cases of gonorrhea and one case of syphilis were found in 2024. Individual knowledge and attitudes toward the prevention of sexually transmitted diseases (STDs) play an important role in efforts to reduce the prevalence of these diseases. This study aims to determine the relationship between the level of knowledge and attitudes toward STD prevention measures in the Puuwatu Community Health Center working area. The research design used was an analytical survey with a cross-sectional approach. The research sample consisted of 91 respondents who were randomly selected from the community visiting the Puuwatu Community Health Center. Data were collected using a questionnaire that measured the level of knowledge, attitudes, and preventive actions for STIs. Data analysis was performed using the chi-square test to identify the relationship between the variables of knowledge, attitudes, and preventive actions. The results showed that there was a significant relationship between the level of knowledge (p=0.000) and attitude (p=0.002) towards PMS prevention measures. People with better knowledge about PMS tended to have a more positive attitude and took preventive measures more often. These findings suggest the need to improve health education programs that emphasize the importance of accurate knowledge and a positive attitude in PMS prevention in the region.